2019
DOI: 10.1039/c9na00385a
|View full text |Cite
|
Sign up to set email alerts
|

A broadband terahertz metamaterial absorber enabled by the simple design of a rectangular-shaped resonator with an elongated slot

Abstract: Broadband metamaterial absorbers are of critical importance in practical applications, but their obtainment approaches are quite complex at present. We demonstrate here that a fairly simple structure design formed by a rectangular-shaped resonator having an elongated slot can be utilized to achieve a broadband absorption response at terahertz frequencies. More than 50% absorption in a continuous frequency range of 1.62 THz (with a central frequency of 2.05 THz) can be gained, and its relative absorption bandwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…In the airborne field, a variety of sound absorption structures such as Helmholtz resonators (Li et al, 2018;Huang et al, 2019) and Fabry-Pérot resonators (Long et al, 2019;Kumar and Lee, 2020;Liu et al, 2020), have shown the capability of perfect and broadband absorption. The emergence of acoustic metamaterials shows a new method for broadband sound absorption (Wang et al, 2019(Wang et al, , 2020(Wang et al, , 2021. Many other metamaterials broadband low-frequency absorbers have been proposed and researched (Mei et al, 2012;Yang et al, 2017;Huang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the airborne field, a variety of sound absorption structures such as Helmholtz resonators (Li et al, 2018;Huang et al, 2019) and Fabry-Pérot resonators (Long et al, 2019;Kumar and Lee, 2020;Liu et al, 2020), have shown the capability of perfect and broadband absorption. The emergence of acoustic metamaterials shows a new method for broadband sound absorption (Wang et al, 2019(Wang et al, , 2020(Wang et al, , 2021. Many other metamaterials broadband low-frequency absorbers have been proposed and researched (Mei et al, 2012;Yang et al, 2017;Huang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The former resonant response may have applications in sensing [11], imaging [12], and color filtering [13], while the latter correspondent is promising in the areas of solar cells [14], photochemical devices [15], hot-electron-based photodetectors [16], and radiative cooling [17]. Such MPAs have been developed from visible [18,19] to terahertz [20,21] and the microwave regions [22,23]. MPAs can be physically realized by suppressing both the transmission and reflection of the incident electromagnetic (EM) waves, simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterial as an artificial medium exhibits some exotic properties such as negative permittivity, negative permeability, negative refractive index, which makes it suitable for various applications such as absorber 1 , microwave imaging 2 , bio sensing 3 , antennas 4 , metamaterial lensing 5 , metamaterial coding 6 , terahertz metamaterial absorber 7 9 , and microwave devices like Bluetooth, WiMAX, GPS 5 , 10 . A negative index metamaterial is present in 11 that consists of elongated beams attached to a plate.…”
Section: Introductionmentioning
confidence: 99%